Herbicides in the Soil Environment: Linkage Between Bioavailability and Microbial Ecology - Zabaloy, Maria Celina (2011)
Modern agriculture relies heavily on herbicides for the control of weeds in crops and pastures to maximize yields and economical benefits to sustain an increasing world population. The introduction of herbicide-resistant traits in several crops, such as glyphosate-resistant soybean, maize and canola, has further increased herbicide consumption worldwide. The environmental fate of herbicides is a matter of recent concern given that only a small fraction of the chemicals reaches the target organisms. While most herbicides are not intentionally applied onto soil, they can enter the soil environment from direct interception of spray by the soil surface during early season or post-harvest applications, from runoff or leaching of the herbicide from vegetation and/or from dead plant material. This chapter will present aspects of the behavior of herbicides in soils, focusing on soil retention and microbial degradation as main factors controlling persistence. The potential impact of herbicides on non-target soil microbes, on their processes and interactions, will be also discussed. The enormous variety of herbicides commercially available today makes it impossible to review all of them. Thus, this work will focus on some of the herbicides most used in the (semiarid) Pampa region of Argentina and worldwide (i.e., glyphosate, 2,4-dichlorophenoxyacetic acid, atrazine, metsulfuron-methyl), based on our own research data. Adsorption to soil is of critical importance for the regulation of herbicide persistence and mobility throughout the environment because sorption processes control the amount of herbicide present in the soil solution. These processes are dependent on several factors related to soil characteristics such as mineral composition, organic matter content, soil solution chemistry and to chemical characteristics of the herbicide. Soil-bound herbicide or residues are temporarily inactivated, which prevents harmful effects on soil biota but also makes them less bio-available for microbial degradation because most microbial species are not able to utilize herbicides in the sorbed state. Herbicide degradation will be discussed both in terms of their use as carbon and nutrient sources. Most isolated herbicide-degrading microorganisms belong to bacterial species, but fungi are also well-known for their capacity to degrade complex substrates, and may be more important than present isolation approaches have suggested. Differential toxicity of herbicides to soil microorganisms may alter community structure, including potential increases in plant or animal pathogens. Herbicides may also cause changes in microbial community function and concomitant impacts on soil health and ecosystem processes.